(untitled) (Modern education and development, 2024)
Ushbu maqolada lingvopragmatika fanining asosiy tamoyillari va uning tilshunoslikdagi ahamiyati yoritilgan. Maqola lingvopragmatikaning nazariy asoslarini bayon qilgan holda, tilning kommunikativ kontekstda qanday ishlatilishi, nutq amallari, yashirin ma’nolar (implicature) va diskurs tahliliga oid masalalarni o‘rganadi. Shuningdek, maqolada lingvopragmatikaning madaniyatlararo muloqotda tutgan o‘rni va turli ijtimoiy kontekstlarda nutqning qanday talqin qilinishi haqida fikr yuritiladi. This article explores the fundamental principles of linguopragmatics and its significance in linguistics. It outlines the theoretical foundations of linguopragmatics, examining how language is used in communicative contexts, issues related to speech acts, implicature, and discourse analysis. Additionally, the article discusses the role of linguopragmatics in intercultural communication and how speech is interpreted across various social contexts.This study serves as a valuable resource for those interested in new approaches within linguistics, highlighting the applications of linguopragmatic analysis in different fields and its importance in fostering effective human communication.